POTENSI SENYAWA ANTI INFLAMASI DARI DAUN SIRSAK (Annona muricata L.) PADA ENZIM COX-2 SECARA IN SILICO - Syaiful Prayogi; Teguh Hary Kartono; Luthfi Hidayat Maulana; Miftahul Saldi; Yulita Amelia (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2026)
Inflammation is still a major cause of death in the world, especially in tropical regions (including Indonesia). The use of non-steroidal anti-inflammatory drugs (NSAIDs) has many side effects and is even toxic. Efforts to find drugs with low toxic effects require long stages and high costs. This effort can be accelerated with a computational approach in the early stages of drug development through the CADD technique by minimizing the risk of failure in later stages. The protein that plays a role in delaying inflammation is the cyclooxygenase (COX) enzyme. Inhibition of COX-2 has much lower side effects than inhibition of COX-1. COX-2 is induced by inflammatory stimuli expressed in synovial cells, leukocytes, fibroblasts, and macrophages, therefore becoming one of the target proteins in inflammation. Natural compounds of the phenolic, flavonoid, and alkaloid groups have been reported to have potential as anti-inflammatories. Soursop leaves are known to be rich in flavonoids. The empirical efficacy of soursop leaves (Annona muricata L.) has been known by the Indonesian people in the treatment of rheumatism or rheumatoid arthritis, anti-inflammatory, antipyretic, and analgesic. This study was conducted in silico with a molecular docking approach using iGemDock v2.1 software. The binding between ligand-target (COX enzyme) was evaluated using Discovery Studio Visualizer. The results showed that all test compounds inhibited COX-2, the isohamnetin 3 robinobioside compound has the potential to be a selective inhibitor of COX-2 when compared to other test compounds and with a reference drug (ibuprofen).